2009
DOI: 10.1002/jcb.22136
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a phosphorylated p130Cas substrate domain attenuates the phosphatidylinositol 3‐kinase/Akt survival pathway in tamoxifen resistant breast cancer cells

Abstract: Elevated expression of p130Cas/BCAR1 (breast cancer anti estrogen resistance 1) in human breast tumors is a marker of poor prognosis and poor overall survival. Specifically, p130Cas signaling has been associated with antiestrogen resistance, for which the mechanism is currently unknown. TAM-R cells, which were established by long-term exposure of estrogen (E2)-dependent MCF-7 cells to tamoxifen, displayed elevated levels of total and activated p130Cas. Here we have investigated the effects of p130Cas inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 49 publications
(52 reference statements)
1
28
0
Order By: Relevance
“…In feline and canine breast cancers the levels of p130 Cas positively correlate with advanced breast disease as well (Scibelli et al 2003). Furthermore, our in vitro studies have shown increased p130 Cas levels in the tamoxifen resistant breast cancer cells TAM-R (Soni et al 2009), which were derived from tamoxifen sensitive MCF-7 cells (Knowlden et al 2003). In 2000, Brinkman and colleagues identified the gene of p130 Cas , in a retroviral insertion screen as a factor that mediates resistance to tamoxifen in breast cancer cell lines (Brinkman et al 2000;Dorssers et al 1993).…”
Section: Involvement Of Cas Family Members In Mammary Carcinomasmentioning
confidence: 76%
See 4 more Smart Citations
“…In feline and canine breast cancers the levels of p130 Cas positively correlate with advanced breast disease as well (Scibelli et al 2003). Furthermore, our in vitro studies have shown increased p130 Cas levels in the tamoxifen resistant breast cancer cells TAM-R (Soni et al 2009), which were derived from tamoxifen sensitive MCF-7 cells (Knowlden et al 2003). In 2000, Brinkman and colleagues identified the gene of p130 Cas , in a retroviral insertion screen as a factor that mediates resistance to tamoxifen in breast cancer cell lines (Brinkman et al 2000;Dorssers et al 1993).…”
Section: Involvement Of Cas Family Members In Mammary Carcinomasmentioning
confidence: 76%
“…Consistently, interference with p130 Cas signaling results in the attenuation of the ERK and PI3K/Akt survival pathways in breast cancer cells (Soni et al 2009). Moreover, overexpression of p130 Cas mediates resistance to the chemotherapeutic drug adriamycin in mammary tumor cells by activating c-Src, Akt, and ERK1/2 growth and survival pathways (Ta et al 2008).…”
Section: Involvement Of Cas Family Members In Mammary Carcinomasmentioning
confidence: 83%
See 3 more Smart Citations